An investigation of the relationship between Corporate Social Responsibility (CSR) and financial performance of companies listed on the Johannesburg Stock Exchange (JSE) in South Africa - Soko, Leon Lenny Kudzaishe (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
The purpose of this study is to investigate whether there is an association between CSR and financial performance in South African companies which are listed on the FTSE/JSE SRI Index. Specifically, whether there is a difference in financial performance of companies that perform CSR activities, and those that do not. If so, which direction does this association have? The selection process of companies used in this study will now be explained step-bystep. The JSE SRI Index results show that there were 80 successful constituents as of February 2015 (JSE, 2015). These 80 companies are listed alphabetically in Appendix A, while the top 100 companies as ranked by Turnover are linked in Appendix B. Of these 100 companies, 67 were constituents of the JSE SRI Index continuously in 2015 and are shown in Appendix C. This leaves 33 companies in the top 100 which are not listed on the JSE SRI Index. Companies that were listed on the JSE SRI Index were assumed to be 'good' companies as the listing requirements included the performance of numerous CSR activities such as Employee development, environmental sustainability practices and stakeholder engagement. The financial performance of these 67 companies was compared to the financial performance of the 33 companies that were not listed on the JSE SRI Index which were included in the population sample of one hundred companies. Financial performance was measured using the ratios: Return on Assets and Return on Equity. The data analysis process used in this study was as follows: 1. The ratios for each company were obtained from the iNET (BFA) database, and annual and integrated reports for the period 2011 - 2015 (Appendix D;E;F). 2. The ratios for Non-SRI and SRI companies were then compared for each of the three ratios using a T-Test. The purpose of the T-Test was to show whether there is a difference in the ratios between SRI and Non-SRI companies on a year to year basis. The direction of the difference was shown by whether the SRI ratio was higher than or lower than the Non-SRI ratio. The results of this study do not seem to support any of the CSR theories, as the study concluded that there is no significant difference between the financial performance of companies that perform CSR activities and those that do not. This means that investing in CSR activities does not have a significant effect on the financial performance of a company.
Keywords: Uncatalogued